2013
DOI: 10.3349/ymj.2013.54.3.578
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Characteristics and Molecular Genetic Analysis of Korean Patients with GNE Myopathy

Abstract: PurposeGlucosamine (UDP-N-acetyl)-2-epimerase/N-acetylmannosamine kinase (GNE) myopathy is an autosomal recessive neuromuscular disorder characterized by early adult-onset weakness of the distal muscles of the lower limbs. The clinical spectrum of GNE myopathy varies, and it is not clear how the same GNE gene mutations can result in different phenotypes. Here, we present clinical, pathological and genetic characteristics of twenty-one Korean patients with GNE myopathy.Materials and MethodsTwenty-one GNE myopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 17 publications
4
18
0
1
Order By: Relevance
“…18 Earlier electrophysiological reports of GNE-hIBM included a large case series of 21 Korean patients, most with purely myopathic and only 3 with mixed neurogenic/myopathic MUPs. 26 Pure myopathic changes sparing the quadriceps were also described. 19,21,23 Neurogenic MUPs were reported in 2 additional GNEhIBM cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Earlier electrophysiological reports of GNE-hIBM included a large case series of 21 Korean patients, most with purely myopathic and only 3 with mixed neurogenic/myopathic MUPs. 26 Pure myopathic changes sparing the quadriceps were also described. 19,21,23 Neurogenic MUPs were reported in 2 additional GNEhIBM cases.…”
Section: Discussionmentioning
confidence: 99%
“…13 Reported description of the electromyographic (EMG) findings in genetically proven hIBM patients show some resemblance to those encountered in sIBM with essentially mixed myopathic and neurogenic features. 9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] In this study, we describe the clinical and electrophysiological features of hIBM subjects in comparison with their sIBM counterparts to identify differences that might help the clinical differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the diagnosis of DMRV is not always easy. Expansion of mutational analysis in GNE gene has indicated that DMRV patients often have an atypical clinical presentation that includes proximal muscle weakness [16,26]. Muscle biopsy is necessary for histopathological evaluation, but is a very invasive method.…”
Section: Discussionmentioning
confidence: 99%
“…The mean onset age for these patients were 23.2 (p.V603L) and 30 (p.C44S) years. 33 Cardiac involvement has been reported in a number of GNE myopathy patients, with a higher prevalence (18%) in Japanese patients. 28 Moreover, a recent animal study revealed the important role of GNE in the early development of cardiac muscles.…”
Section: Phenotype Spectrum Of Variantsmentioning
confidence: 99%